Energy for the 21st century a comprehensive guide to conventional and alternative sources - Nersesian, Roy L. (Armonk, N.Y. : M.E. Sharpe, 2007)
Provides a detailed analysis of the past, present, and future of all the principal energy sources--biomass, coal, oil, natural gas, hydro and nuclear power--as well as sustainable sources, especially fuel cell technology.
Ηλεκτρονικό βιβλίο
Keywords: Power resources; Energy policy; Electronic books